Implementasi Program Transformasi "Sentuhan Mahabbah" JKMN Negeri Kedah (Kajian Kes di Taman Sinar Harapan Jitra) - Abdul Rahman, Siddiqi (2012)
Each transformation in the organization have different problems and challenges as still lack of understanding about the functions, duties and responsibilities, creativity, and how to think by some staff.Support the necessary impetus towards motivation is usually done through programs such as training courses, mentoring/coaching, training road map, seminars, workshops and so on. Many motivational program that has been able to transform in the behavior and the organizational culture, but not a bit impressed about the program failed and redundant. JKMN (Social Welfare Department) Kedah has implemented a program of transformation "SentuhanMahabbah" in the the form of training/motivational courses to enhance the consolidation and strengthening of the staff towards the creative and innovative in the institution. This case study aims to identify the implementation of the transformation program “SentuhanMahabbah” at the institution Taman Sinar Harapan (TSH) Jitra, factors are composed of responsive participants, mechanisms, stages of activities, and impact of the programs. Next, simple analysis is done using SWOT and TOWS method to find out its development as proposed front periodically. This study used qualitative methods with a heuristic method that is where researchers affiliated with the research question. Information can be accessed through, observation of program activities, documents, interviews, and questionnaires. Interviews and questionnaires limited to the management of the TSH Jitra, The parties of JKMN Kedah involved with the program, and participants in the program. Overall, the results showed that the implementation of the program is good enough. Finally, several suggestions have been proposed as an alternative for the future